2018
DOI: 10.32832/pkm-p.v2i1.198
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Model Pendidikan Kesehatan Pada Ibu Hamil Untuk Menurunkan Angka Kematian Ibu Di Kabupaten Bogor

Abstract: Permasalahan utama yang dihadapi terkait kesehatan ibu hamil di Indonesia adalah tingginya angka kematian ibu berhubungan dengan persalinan, banyak ibu-ibu menganggap kehamilan sebagai hal biasa, alamiah dan kodrati. Kebanyakan Ibu hamil kurang menyadari pentingnya pemeriksaan kehamilan menyebabkan tidak terdeteksinya faktor risiko yang mungkin dialami ibu hamil, hal ini kemungkinan disebabkan rendahnya tingkat komunikasi, informasi dan edukasi mengenai kesehatan ibu hamil. Pendidikan kesehatan penting untuk m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…All of them are ensuring the availability and management of clean water and sustainable sanitation for all. While the sustainable health development program carried out by the government many programs have not been achieved from the implementation of the MDG's which must be continued by the implementation of the SDG's, such as reducing maternal mortality (MMR), death of newborn children, contracting the HIV / AIDS virus, low knowledge about HIV and AIDS in the population aged 15-24 years, malnutrition experienced by children under five, not fulfilled the needs of family planning (KB) (38) . The principles in the implementation of sustainable development are shown in Figure 1 above, such as universality (Overall), which means that the implementation of sustainable development is not only calculated from the age but is carried out for all ages that have to get prosperity, the second is integration (Integration), namely the implementation of development broadly sustainable integrated into all dimensions such as the economic, social, and environmental dimensions, and the third is no one left behind (Ensuring All Is Not Left Behind) then, the implementation of sustainable development must provide benefits for all not only certain groups that get benefits, especially which is vulnerable and must involve all stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…All of them are ensuring the availability and management of clean water and sustainable sanitation for all. While the sustainable health development program carried out by the government many programs have not been achieved from the implementation of the MDG's which must be continued by the implementation of the SDG's, such as reducing maternal mortality (MMR), death of newborn children, contracting the HIV / AIDS virus, low knowledge about HIV and AIDS in the population aged 15-24 years, malnutrition experienced by children under five, not fulfilled the needs of family planning (KB) (38) . The principles in the implementation of sustainable development are shown in Figure 1 above, such as universality (Overall), which means that the implementation of sustainable development is not only calculated from the age but is carried out for all ages that have to get prosperity, the second is integration (Integration), namely the implementation of development broadly sustainable integrated into all dimensions such as the economic, social, and environmental dimensions, and the third is no one left behind (Ensuring All Is Not Left Behind) then, the implementation of sustainable development must provide benefits for all not only certain groups that get benefits, especially which is vulnerable and must involve all stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…Health education is a long-term behavioral investment as a behavior change process in a person. In a short period (immediate impact), health education produces a change or increase in public knowledge [17]. Knowledge is a factor in the strength of changing attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of research conducted by Krisnita, showed that there was a significant relationship between the history of complications in previous deliveries and the incidence of maternal death. The results of research conducted by Dwi, et al (2008) can be seen that the factors that jointly influence maternal mortality are obstetric complications, history of disease and history of childbirth (Baeva et al, 2018;King & Bushwick, 2017;Nur et al, 2018;Sasnitiari & Puspitasari, 2019).…”
Section: Discussionmentioning
confidence: 99%